A Comparative Study of Structural and Ethanol Gas Sensing Properties of Pure, Nickel and Palladium Doped SnO2 Nanorods Synthesised by the Hydrothermal Method - Inderan, Vicinisvarri; Arafat, M.M.; Haseeb, A.S. Md. Abdul; Sudesh, Kumar; Lee, Hooi Ling (Penerbit Universiti Sains Malaysia, 2019)
SnO2 nanostructures are usually modified with some metal dopants in order to improve its gas sensing properties. In this work, pure tin oxide (SnO2), nickel (Ni) doped SnO2 (Ni:SnO2) and palladium (Pd) doped SnO2 (Pd:SnO2) nanorods were successfully synthesised via hydrothermal method at low temperature (180°C) without templates or further calcination. All the samples were systematically analysed using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM). The sensor response (R = R0/Rg) towards 1000 ppm ethanol gas was investigated using nitrogen gas as a carrier gas. XRD results confirmed that all samples consisted of rutile tetragonal-shaped SnO2. It was found that the average diameter of nanorods formed in Ni:SnO2 and Pd:SnO2 were decreased to ~6 nm and ~10 nm, compared with nanorods formed in pure SnO2 (~25 nm). The gas sensing results indicated that the sensor properties of SnO2 were enhanced after the doping process. At 450°C, the Pd:SnO2 nanorod sensor recorded the highest response value towards 1000 ppm ethanol gas which is 15 times higher than pure SnO2 nanorods. Interestingly, all samples showed similar response time, ~ 40 s. However, pure SnO2 and Ni:SnO2 nanorods sensors exhibited longer recovery time compared to Pd:SnO2 nanorods. Pd:SnO2 nanorods recorded only 12 min of almost 100% recovery. It is proposed that Pd:SnO2 sensor could be a promising candidate for the detection of ethanol gas. © Penerbit Universiti Sains Malaysia, 2019.